Feedback Seeking Exploration Study on Entrepreneurial Project (Academic) Performance - Indudewi, Febe Yuanita Ratna; Subadi, Lucky Cahyana (Review of Management and Entrepreneurship, 2018)
In the era of competence, performance becomes highly appreciated for being an embodiment of selfcompetence. Increased competence and performance achievement is a process that involves the other party. Feedback seeking behaviour is assumed to be a variable that will affect the process of increasing competence and performance, especially in a learning process. This research aimed to see the correlation between feedbacks seeking behaviour to student’s academic performance. An effective feedback from their mentor can influence student’s academic performance in a positive way. A quantitative-descriptive design was used in this research. A random sampling questionnaire and secondary data from Entrepreneurship 2 program of Universitas Ciputra such as overall student’s grades were used to obtain the result. The finding of this research consequently helps the lecturers to design a better feedback giving and seeking behaviour.